STUDY ON FATIGUE LIFE OF HYDRAULIC TENSION BAR OF SHEARERS - HAO ZhiYong; LEI YaoLong; MAO Jun; ZHANG FengJia (Jixie qiangdu)
In order to study on the loading spectrum and fatigue life of hydraulic tension bars on shears,this paper solves the spatial mechanic problems of hydraulic tension bars by constructing spatial mechanical model and using partitioned matrix element segmentation method. Using experiment to test the operating load of hydraulic tension bars,this paper chooses the worst loaded one to simulate the fatigue life. The result indicates that the stress concentration part of hydraulic tension bar locates on the root of the first screw thread. The maximum stress point is close to the end point at the root of the first thread tooth,of which the number is 1386 MPa,the triple thread teeth bear over 50% of the full load; the position on which fatigue crack occurs first is at the root of the thread teeth in the screw part of the hydraulic tension bar; assuming that the daily continuously working time for shear is 12 hours,the hydraulic tension bar starts to crack at the 53 rdday. This research provides load data for hydraulic tension bar structural design,and also offers a new method of operating load monitor for shears.